The impact of ir 4.0 technology acceptance on small medium enterprises behavior intention in the halal food and beverage industry in malaysia: a pilot study - Mokhtar, Mazita; Yahya, Salme; Ali Khan, Muhammad Waris; Kamaruzzaman, Zetty Ain (Institut Pariwisata dan Bisnis Internasional, 2022)
This pilot study implemented Venkatesh, Morris, Davis and Davis (2003)'s model of Unified Theory of Acceptance and Use of Technology (UTAUT) in the field of halal food and beverage enterprises in Malaysia. 30 sets of questionnaires have been sent to participants which are from the management level in food and beverage establishment. The questionnaire is organized in eight parts and used 5 point Likert scale. The research variables are effort expectancy, performance expectancy, facilitating condition, social influence, price value and muamalat e-commerce. The dependent variable is Small Medium Enterprise (SME) behavior intention in halal food and beverage establishment. The findings highlighted the question items that performed and thus should be kept, as well as the question items that performed badly and should be discarded or studied further. Statistical Program for Social Science (SPSS) version 26 was also used to do a reliability analysis and factor analysis. The findings revealed that the data is trustworthy and has a fair level of normality. In the future, this pilot study will be followed by a full study.This pilot study implemented Venkatesh, Morris, Davis and Davis (2003)'s model of Unified Theory of Acceptance and Use of Technology (UTAUT) in the field of halal food and beverage enterprises in Malaysia. 30 sets of questionnaires have been send to participant which are from the management level in food and beverage establishment. The questionnaire is organized in eight parts and used 5 point Likert scale. The research variables are effort expectancy, performance expectancy, facilitating condition, social influence, price value and muamalat e-commerce. The dependent variable is Small Medium Enterprise (SME) behavior intention in halal food and beverage establishment. The findings highlighted the question items that performed and thus should be kept, as well as the question items that performed badly and should be discarded or studied further. Statistical Program for Social Science (SPSS) version 26 was also used to do a reliability analysis and factor analysis. The findings revealed that the data is trustworthy and has a fair level of normality. In the future, this pilot study will be followed by a full study.